2018
DOI: 10.1177/1535370218782139
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol-A alters microbiota metabolites derived from aromatic amino acids and worsens disease activity during colitis

Abstract: Inflammatory bowel disease is a complex collection of disorders. Microbial dysbiosis as well as exposure to toxins including xenoestrogens are thought to be risk factors for inflammatory bowel disease development and relapse. Bisphenol-A has been shown to exert estrogenic activity in the colon and alter intestinal function, but the role that xenoestrogens, such as bisphenol-A , play in colonic inflammation has been previously described but with conflicting results. We investigated the ability of bisphenol-A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 55 publications
2
40
0
Order By: Relevance
“…Some endocrine compounds could induce alterations in the gut microbiota and the metabolites they produce, which may be associated with increased inflammation [97]. …”
Section: Functional Pathwaysmentioning
confidence: 99%
“…Some endocrine compounds could induce alterations in the gut microbiota and the metabolites they produce, which may be associated with increased inflammation [97]. …”
Section: Functional Pathwaysmentioning
confidence: 99%
“…It should be noted that previous studies have reported that BPA may change intestinal nociception and impair the gut barrier function . It is also known that this substance can alter intestinal microbiota metabolism and is involved in pathogenesis of the inflammatory bowel disease . However, knowledge concerning BPA‐induced changes in the neurochemical characterization of the enteric neurons is rather scanty and limited to the ENS in the duodenum and ileum 4.…”
Section: Introductionmentioning
confidence: 99%
“…1,30 It is also known that this substance can alter intestinal microbiota metabolism and is involved in pathogenesis of the inflammatory bowel disease. 5,31,32 However, knowledge concerning BPA-induced changes in the neurochemical characterization of the enteric neurons is rather scanty and limited to the ENS in the duodenum and ileum 4. Therefore, the aim of this study was to investigate the changes caused by various doses of BPA on the ENS in the jejunum-the part of the intestine where the bulk of this substance occurring in the food is absorbed.…”
mentioning
confidence: 99%
“…Some Bifidobacterium strains have been shown to exert health-promoting effects and is included in a number of probiotic foods and supplements [97]. DeLuca et al (2018) [46] used a dextran sulphate sodium-induced colitis model in female C57BL/6 mice and found that BPA exposure at 50 µg/kg/day negatively affects gut physiology by reducing microbiota metabolites derived from aromatic amino acids, which might be associated with autoimmune diseases, specifically with inflammatory bowel disease. This dose was selected because it is the EPA reference dose for BPA.…”
Section: Bpa Exposure Induced Significant Decrease Inmentioning
confidence: 99%